Respostas

2014-06-19T12:42:40-03:00
2x + y = 10     *(2) multiplicando 
3x - 2y = 1

4x +2y = 20    
3x - 2y = 1
7x        =21
x=21/7
x=3

substitundo x=3 em:
2x + y = 10
2.3+y=10
6+y=10
y=10-6
y=4
___________________________________________________________
2x + 3y = 10   
4x + y = -1         *(-3)    

  2x + 3y = 10   
-12x -3y = 3 
-10x      =13    (-1)
10x=-13
x=-13/10

substituindo x=-13/10 em:
2x + 3y = 10 
2.(-13/10)+3y=10
-26/10+3y=10
3y=10+26/10
3y=126/10
y=(126/10)*(1/3)
y=126/30
y= 21/5
__________________________________________________
x + y = 7
2x/5 = 3y/y

x+y=7
2x/5=3      ==>  2x/5=3     x=3/ (2/5)    x=3.5/2   x=15/2
 
substituindo x= 15/2 em:
x+y=7
15/2+y=7
y=7-15/2
y=-1/2
__________________________________________
5(x + 1) + 3(y - 2) = 4
8(x +1) + 5(y - 2)= 9

5x+5+3y-6=4
8x+8+5y-10=9

5x+3y=4+1
8x+5y=9+2

5x+3y=5
8x+5y=11

5x+3y=5
5x=5-3y
x=(5-3y)/5

substituindo em :
8x+5y=11
8(5-3y)+5y=11
     5
40-24y+5y=11
    5

40-24y+25y=55
           5

40+y=55
y=55-40
y=15

substituindo o valor de y=15 em:

x=(5-3y)/5
x=(5-3.15)/5
x=(5-45)/5
x=-40/5
x=-8
4 2 4